Effectiveness of Murottal Therapy on Blood Pressure Reduction in Hypertensive Patients: A Systematic Review - Konita, Nisya; Falah, Miftahul (LPPM STIKes Muhammadiyah Ciamis, 2025)
Hypertension is a non-communicable disease with the highest incidence and mortality rate in the world. This study aims to evaluate the effectiveness of murottal therapy on reducing blood pressure in hypertensive patients. This research method uses a systematic review method, with data sources coming from Google Scholar and Garuda Portal. Articles were taken according to the inclusion criteria, namely Quasy-experiment design research, involving hypertensive patients, and full-text articles published in the period 2020-2024. Exclusion criteria included articles that did not meet the full research structure, review-based articles, or articles with content that was not relevant to the topic. From the search results there were 1,414 articles, then there were articles that were in accordance with the research topic and the final analysis results were six relevant articles analyzed using the PRISMA framework. The results of the review showed that murottal therapy was effective in reducing blood pressure, accompanied by significant statistical test results on upper (systole) and lower (diastole) pressure. This therapeutic effect is thought to be related to the ability of murottal to provide relaxation, reduce anxiety, and stabilize hormones that affect blood pressure. This study recommends murottal therapy as a non-pharmacological approach to help manage hypertension.